TLR4 and MMP2 polymorphisms and their associations with cardiovascular risk factors in susceptibility to aortic aneurysmal diseases. Issue 1 (8th January 2019) - Li, Tan; Jing, Jingjing; Sun, Liping; Jiang, Bo; Xin, Shijie; Yang, Jun; Yuan, Yuan
Abstract : Background: Toll-like receptor 4 (TLR4) and matrix metalloproteinase 2 (MMP2) play important roles in aortic pathophysiology. We aimed to evaluate the contribution of TLR4 and MMP2 polymorphisms individually and complex interactions between gene and risk factors in susceptibility to aortic aneurysm (AA) and its subtypes.Methods: KASP method was adopted to detect TLR4rs11536889, rs1927914 and MMP2rs2285053 polymorphisms in 498 controls and 472 AA patients, including 212 abdominal AA (AAA) and 216 thoracic AA (TAA).Results: In the overall analysis, MMP2rs2285053 TC genotype was correlated with TAA risk ( P = 0.047, OR = 1.487). Stratified analysis revealed an increased AA risk in males with TLR4rs1927914 TC genotype, while MMP2rs2285053 TC conferred an elevated AA risk in the subjects ≤60 years, and its TC genotype and dominant model were associated with TAA in the subjects ≤60 year. The interaction between TLR4rs1927914 and MMP2rs2285053 was associated with AAA risk ( P interaction = 0.028, OR = 2.913). Furthermore, significant interaction between TLR4rs11536889 and dyslipidemia was observed for TAA risk, while TLR4rs1927914 could interact with hypertension and diabetes to increase the risk of AA or its subtypes. Two-way interaction effect of TLR4rs1927914 and MMP2rs2285053 was enhanced by diabetes or dyslipidemia.Conclusion: TLR4 and MMP2 polymorphisms and their complex interactions with cardiovascular risk factors contributed to aortic aneurysmal diseases.